Determinants of self-perceived health for Canadians aged 40 and older and policy implications - William Ian Andrew Bonner; Robert Weiler; Rotimi Orisatoki; Xinya Lu; Mustafa Andkhoie; Dana Ramsay; Mohsen Yaghoubi; Megan Steeves; Michael Szafron; Marwa Farag (BMC, 2017)
Abstract Background Perceived health status indicates people's overall perception of their health, including both physical and psychological dimensions. The aim of this study was to examine the determinants of self-perceived health for Canadians aged 40 and older using data from the Canadian Community Health Survey (2010). Methods Multiple logistic regression models were employed to identify factors associated with self-perceived health in two age groups: Adults aged 65+ and Adults aged 40-64. Results We found that higher income was significantly associated with better health status while chronic conditions and stress were associated with worse health status. In the 40-64 and 65+ age groups, individuals in the highest income bracket were 4.65 and 1.94 times, respectively, more likely to report better health than individuals in the lowest income bracket. The difference in the level of income associated health inequities between the two age groups point to the need for understanding the reasons behind lower inequities among seniors and how much the social protections provided by the Canadian government to seniors contribute to lowering inequities. Conclusions Though Canada has a national public health insurance system providing coverage to all Canadians, health inequities associated with income persist providing further evidence of the importance of the social determinants of health. Examining the extent of these inequities and what factors influence them helps direct policy attention. In addition to documenting inequities, this paper discusses policy options for reducing the identified inequities.